Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/mpg.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies a Novel FOXP3 Mutation in a 2‐Generation Family With Inflammatory Bowel Disease

Abstract: Objectives Inflammatory bowel disease (IBD) is heritable, but a total of 163 variants commonly implicated in IBD pathogenesis account for only 25% of the heritability. Rare, highly penetrant genetic variants may also explain mendelian forms of IBD and some of the missing heritability. To test the hypothesis that rare loss-of-function mutations can be causative, we performed whole exome sequencing (WES) on 5 members of a 2-generation family of European ancestry presenting with an early-onset and atypical form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 44 publications
0
30
0
1
Order By: Relevance
“…The specific VEO phenotypes often include manifestation of known monogenic diseases and the first case of the Mendelian form of VEO IBD was confirmed as a mutation in the IL10R gene (30) that underlined an association of IBD with primary immunodeficiency. Recently, a novel FOXP3 mutation was also identified in a two-generation family with early onset phenotypes similar to IBD (67), thus lending support to the manifestation of Mendelian disease in IBD cases. Many monogenic disease genes have been shown to confer overlapping pathology with IBD (known as IBD-like pathogenesis) and are seen more frequently in VEO cases (69).…”
Section: Monogenetic Disorders and Association With Very Early Onset Ibdmentioning
confidence: 93%
See 1 more Smart Citation
“…The specific VEO phenotypes often include manifestation of known monogenic diseases and the first case of the Mendelian form of VEO IBD was confirmed as a mutation in the IL10R gene (30) that underlined an association of IBD with primary immunodeficiency. Recently, a novel FOXP3 mutation was also identified in a two-generation family with early onset phenotypes similar to IBD (67), thus lending support to the manifestation of Mendelian disease in IBD cases. Many monogenic disease genes have been shown to confer overlapping pathology with IBD (known as IBD-like pathogenesis) and are seen more frequently in VEO cases (69).…”
Section: Monogenetic Disorders and Association With Very Early Onset Ibdmentioning
confidence: 93%
“…Since then, WES has successfully identified rare functional variants in novel genes implicated in the pathogenesis of VEO ( FOXP3 (67), IL10RB (30, 56) and XIAP (66) genes) or even adult ( GSDMB (54) and NDP5 2 genes (61)) IBD. WES is therefore the most current cost effective technology capable of exposing low to intermediate frequency variants that may have higher effect size than the weaker associations reported by common GWAS variants.…”
Section: Sequencing In Ibd Genetic Studies: Progressmentioning
confidence: 99%
“…Importantly, XIAP is a positive regulator of NOD2 function 60 , and so therefore, loss-of-function mutations in XIAP would result in similar functional effects as those observed with NOD2 mutations. Subsequent successful application of WES has identified more rare functional variants in novel genes implicated in the pathogenesis of VEO ( FOXP3 61 , IL10RB 62 ; 63 and adult onset ( GSDMB 64 and NDP5 2 genes 65 ) IBD.…”
Section: Common and Rare Ibd Genetic Variation: Sequencing Studies Inmentioning
confidence: 99%
“…81 One example of successful exome sequencing is the discovery of a novel A-to-C missense variant (c.694A>C) in exon 6 of the FOXP3 gene on chromosome X in VEO IBD. 82 Interestingly, GWAS-based studies have shown that a substantial proportion of IBD-associated loci are located in non-coding regions, suggesting rare variants regulating gene expression may also be important in IBD pathogenesis. 8 The roles of non-coding regions on their pathogenic effects through modulation of gene expression are being identified by expression quantitative trait loci (eQTL)-GWAS mapping analysis.…”
Section: Current Status Of Genetic Research For Ibdmentioning
confidence: 99%